1986
DOI: 10.1177/0146167286121011
|View full text |Cite
|
Sign up to set email alerts
|

The Loneliness Experience of College Students

Abstract: The present study examined sex differences among college students in the quantitative and qualitative aspects of loneliness. Measurements of loneliness, emotional reactivity, and social risk taking were administered to 112 undergraduates. Males evidenced greater self-reported loneliness than females. Generally, affective and social risk-taking measures were more highly related to loneliness among males than females. The results suggest that loneliness is more likely to be associated with negative personal and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
25
0
2

Year Published

1990
1990
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 13 publications
7
25
0
2
Order By: Relevance
“…These findings of the study are consistent with several other studies (Chen & Chung, 2007;Brage et al, 1994;Demir, 1990;Girgin, 2009;Norman & DeWayne, 1986;Wiseman & Guttfreund, 1995). On the other hand, in their studies, Terrell et al (2000) and Woodward and Frank (1988) reported that females are lonelier.…”
Section: Discussionsupporting
confidence: 92%
“…These findings of the study are consistent with several other studies (Chen & Chung, 2007;Brage et al, 1994;Demir, 1990;Girgin, 2009;Norman & DeWayne, 1986;Wiseman & Guttfreund, 1995). On the other hand, in their studies, Terrell et al (2000) and Woodward and Frank (1988) reported that females are lonelier.…”
Section: Discussionsupporting
confidence: 92%
“…We were able to find more detailed information on the participants' self-perceptions using Marsh and O'Neill's (1 984) well-established multidimensional self-concept measure. Consistent with prior research, our results showed that lonely people had lower or more negative self-perceptions than nonlonely people (Goswick & Hojat, 1982;Inderbitzen-Pisaruk, Clark, & Solano, 1992;Jones et al, , 1983Kamath & Kanekar, 1993;Lamm & Stephan, 1987;Schultz & Moore, 1986). In comparison, lonely people were found to rate themselves lower in physical appearance, emotional stability, same gender and opposite gender relations, relations with parents, and general self-concept.…”
Section: Discussionsupporting
confidence: 90%
“…This interpretation accounts for the unexpected relationship between negative social appraisal and lower perceived stress. However, by maintaining a more independent self-construal, men may also view a lack of connectedness more strongly as a social stigma and specifically as a personal failure (Schultz & Moore, 1986), hence the stronger negative relationship between social connectedness and perceived stress.…”
Section: Discussionmentioning
confidence: 99%